POPULATION DYNAMIC AND SPAWNING POTENTIAL RATIO OF SHORT MACKEREL (Rastrelliger brachysoma Bleeker, 1851) IN THE NORTHERN COAST OF JAVA - Achmad Zamroni; Tri Ernawati (Research Center for Fisheries, 2019)
Short mackerel fish (Rastrelliger brachysoma) is one of small pelagic fish mostly exploited by mini purse seine fishing gear. Exploitation of short mackerel by mini purse seine has an increasing trend every year and suspected to have negative impacts. One of the negative impact is the decrease of fish abundance, so it is necessary to carry out population dynamics and Spawning Potential Ratio (SPR) studies through length-based approach to provide exploitation indicator as biology reference point. The result of length-weight relationship analysis shows that the growth pattern (b = 2.3483) is negative allometry. The estimated length at first capture and its first sexual maturity analysis shows that the value of length at first capture (Lc = 15.4 cm FL) is greater than the length at first sexual maturity (Lm = 15.21 cm FL). The estimated maximum length (L∞) is 21.05 cm FL with growth rates (K) is 1.01 year-1 and t0 at -0.177 years. The estimated total mortality (Z) was 5.48 year-1, natural mortality (M) was 2.02 year-1 and fishing mortality (F) was 3.46 year-1. The predicted exploitation rate (E) is 0.63 which higher than the optimum value (E = 0.5). The estimated length-based SPR (LB-SPR) of 30% (SPR > 20% or above limit) means that short mackerel fishing activity has full exploitation.